2012
DOI: 10.1016/j.nimb.2012.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion induced surface and microstructural evolution in metallic glass thin films

Abstract: a b s t r a c tSwift heavy ion induced changes in microstructure and surface morphology of vapor deposited Fe-Ni based metallic glass thin films have been investigated by using atomic force microscopy, X-ray diffraction and transmission electron microscopy. Ion beam irradiation was carried out at room temperature with 103 MeV Au 9+ beam with fluences ranging from 3 Â 10 11 to 3 Â 10 13 ions/cm 2 . The atomic force microscopy images were subjected to power spectral density analysis and roughness analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 28 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Surface morphology evolution of the ion beamirradiated solid material was caused by competition between ion bombardment-inducing roughness and internal material transportation-inducing smoothness [33]. The metallic glass surface was smooth because of its disordered structure, without the orientation-dependent sputtering phenomenon in crystal materials [34].…”
Section: Discussionmentioning
confidence: 99%
“…Surface morphology evolution of the ion beamirradiated solid material was caused by competition between ion bombardment-inducing roughness and internal material transportation-inducing smoothness [33]. The metallic glass surface was smooth because of its disordered structure, without the orientation-dependent sputtering phenomenon in crystal materials [34].…”
Section: Discussionmentioning
confidence: 99%
“…The increased roughness at high fluence irradiation can be explained by the collision cascade as a result of Ni ion‐benzil interactions. The energy received by the displaced atoms is higher than the binding energy and the atoms leave the surface overcoming the energy barrier …”
Section: Resultsmentioning
confidence: 99%
“…ξ for pristine film, and for films annealed at 400°C and 600°C are 1.6, 1.8 and 2.1, respectively. Herring and Mullins have reported the possible surface mechanism as plastic flow driven by surface tension, evaporation condensation, volume diffusion and surface diffusion for ξ values 1, 2, 3 and 4 [21,28,29]. The ξ values increases on annealing.…”
Section: Surface Analysismentioning
confidence: 99%
“…Senoy et al and Hysen et al reported the fabrication of thin films from composite targets using vacuum evaporation [19,20]. They also studied annealing and swift heavy ion irradiation effects on these films and reported the formation of Fe-Ni nanocrystals with annealing [21,22]. These nanocrystalline structures precipitate after annealing at 400°C.…”
mentioning
confidence: 99%